Long-read sequencing technology indicates genome-wide effects of non-B DNA on polymerization speed and error rate - Guiblet, Wilfried M; Cremona, Marzia A; Cechova, Monika; Harris, Robert S; Kejnovská, Iva; Kejnovsky, Eduard; Eckert, Kristin; Chiaromonte, Francesca; Makova, Kateryna D (Genome research, 2018)
DNA conformation may deviate from the classical B-form in ∼13% of the human genome. Non-B DNA regulates many cellular processes; however, its effects on DNA polymerization speed and accuracy have not been investigated genome-wide. Such an inquiry is critical for understanding neurological diseases and cancer genome instability. Here, we present the first simultaneous examination of DNA polymerization kinetics and errors in the human genome sequenced with Single-Molecule Real-Time (SMRT) technology. We show that polymerization speed differs between non-B and B-DNA: It decelerates at G-quadruplexes and fluctuates periodically at disease-causing tandem repeats. Analyzing polymerization kinetics profiles, we predict and validate experimentally non-B DNA formation for a novel motif. We demonstrate that several non-B motifs affect sequencing errors (e.g., G-quadruplexes increase error rates), and that sequencing errors are positively associated with polymerase slowdown. Finally, we show that highly divergent G4 motifs have pronounced polymerization slowdown and high sequencing error rates, suggesting similar mechanisms for sequencing errors and germline mutations.
Keywords: kinetika; Sequence Analysis, DNA; konformace nukleové kyseliny; Reproducibility of Results; Nucleic Acid Conformation; genomika; reprodukovatelnost výsledků; DNA; DNA Replication; replikace DNA; mutace; G-kvadruplexy; Mutation; Genomics; Humans; High-Throughput Nucleotide Sequencing; nukleotidové motivy; Kinetics; vysoce účinné nukleotidové sekvenování; sekvenční analýza DNA; G-Quadruplexes; Nucleotide Motifs; lidé